2010
DOI: 10.1038/ki.2010.257
|View full text |Cite
|
Sign up to set email alerts
|

Selective deletion of Connexin 40 in renin-producing cells impairs renal baroreceptor function and is associated with arterial hypertension

Abstract: Renin-producing juxtaglomerular cells are connected to each other and to endothelial cells of afferent arterioles by gap junctions containing Connexin 40 (Cx40), abundantly expressed by these two cell types. Here, we generated mice with cell-specific deletion of Cx40 in endothelial and in renin-producing cells, as its global deletion caused local dissociation of renin-producing cells from endothelial cells, renin hypersecretion, and hypertension. In mice lacking endothelial Cx40, the blood pressure, renin-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
87
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 23 publications
2
87
2
1
Order By: Relevance
“…Deletion of Cx40 in reninproducing but not in endothelial cells resulted in hyperreninemia and hypertension (17,30). Kurt et al (17) also reported that there is a "reciprocal expression of Cx40 and Cx45 during phenotypical changes in renin-secreting cells".…”
mentioning
confidence: 97%
“…Deletion of Cx40 in reninproducing but not in endothelial cells resulted in hyperreninemia and hypertension (17,30). Kurt et al (17) also reported that there is a "reciprocal expression of Cx40 and Cx45 during phenotypical changes in renin-secreting cells".…”
mentioning
confidence: 97%
“…15 Interestingly, both Cx40A96S mice and mice with renin cell-specific deletion of Cx40 maintain the ability to recruit additional renin-producing cells in response to salt depletion and treatment with an angiotensin converting enzyme (ACE) inhibitor, while those with global deletion of Cx40 do not. 3,5,6 These observations suggest that gap junctional coupling is not required for recruitment of additional renin cells during homeostatic challenges, but it appears to be necessary for proper localization of these cells both under basal conditions and during prolonged renin stimulation. It is also possible that a structural or scaffolding function of Cx40 hemi-channels in nonrenin cells 16 may be required for this process.…”
mentioning
confidence: 78%
“…8 Disruption of Cx40 leads to loss of pressure control of renin secretion and development of hypertension. 6,5,3 In this issue of JASN, Lubkemeier et al 8 report their findings in a new transgenic mouse model that expresses a missense mutation in exon 2 of the connexin40 gene (Cx40A96S). This same loss-of-function mutation was previously identified in a human patient with idiopathic atrial fibrillation.…”
mentioning
confidence: 99%
See 2 more Smart Citations